Implementasi Manajemen Kinerja Pemasaran pada Asuransi - Aisha Alvia; Rina Aldila; Yohana Ariska Putri Nasution; Zainarti Zainarti (Khidmatussifa: Journal of Islamic Studies, 2023)
Businesses must retain their clients to remain profitable. The academic field of management marketing considers customer relationship management (CRM) to be best suited to achieve this, whereas communications management focuses more on public relations (PR). The aim of this study is to analyze theories in the two disciplines and derive a theory that integrates CRM and PR client retention frameworks. The framework was then tested in-depth interviews with short-term insurance clients and short-term insurance providers (brokers and direct insurance) in South Africa to obtain perspectives from both parties. The importance of some of the fundamental elements found in the literature is emphasized, the importance of two elements is questioned and it is established that there are three inconsistencies between what providers consider important for clients to retain and what clients consider necessary for them to remain in a relationship with the insurer. This probably explains the many failed client retention attempts of South African brokers and direct insurers. Six new CRM and/or PR elements, not found in the literature, are presented in the article for exploration in future research. To assist client retention in the highly competitive short-term insurance industry, the results are applied to the core principles of Niemann's (2005) SA strategic integrated communication (IC) implementation model. Finally, the authors present an integrated approach to client retention strategy in the South African short-term insurance industry, combining marketing and communication theory. Keywords: insurance, work management,